The Development of Digital Comics Learning Media Based Ethnomathematics of Kretek Dance Integrated with Islamic Values - Arthamevia, Arnetta Thalia; Wahyuni, Fina Tri; Mursyid, Achmad Yafik (Jurnal Pendidikan Matematika, 2022)
The Indonesian education system has come in the era of the industrial revolution 4.0, so the development of learning media should be carried out according to technological developments with upholding Indonesian cultural values and religious character to achieve the noble goals of education. Media development is carried out to overcome students' difficulties in learning mathematics, one of which is the angle material that requires visualization. One of the visual media is digital comics. This study aims to determine the development process and the feasibility of developing digital comic learning media based on the ethnomathematics of kretek dance that integrates Islamic values. This study used a Research and Development (R&D) type with a Four-D (4D) model that used a limited-scale trial. The model consists of four stages: define, design, develop, and disseminate. The results of this study were obtained by expert validation sheets and student response questionnaires as users. The research results from the three experts showed that the criteria were very feasible, with an average of 88.89% for material experts, 82.78% for media experts, and 95% for Islamic value integration experts. A limited-scale product trial conducted on 10 grade VII students of MTs NU Hasyim Asy'ari 03 Kudus obtained a percentage average of 98% with the criteria very feasible. Thus, the digital comic learning media developed in this study was very feasible to be used in mathematics learning. This research can encourage teachers to explore more about learning media that will be used to help transfer academic knowledge to students. Sistem pendidikan Indonesia telah memasuki era revolusi industri 4.0 sehingga pengembangan media pembelajaran hendaknya dilakukan sesuai perkembangan teknologi dengan tetap menjunjung tinggi nilai budaya Indonesia dan karakter religious sebagai usaha untuk mencapai tujuan luhur pendidikan. Pengembangan media dilakukan untuk mengatasi kesulitan siswa dalam pembelajaran matematika, salah satunya yakni pada materi sudut yang memerlukan visualisasi. Salah satu media visual yang dapat digunakan yakni komik digital. Penelitian ini bertujuan untuk mengetahui proses pengembangan dan kelayakan hasil pengembangan media pembelajaran komik digital berbasis etnomatematika tari kretek yang terintegrasi nilai keislaman. Penelitian ini menggunakan jenis penelitian Research and Development (R&D) dengan model pengembangan Four-D (4D) yang menggunakan uji coba skala terbatas. Model ini terdiri dari empat tahapan yaitu pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Hasil penelitian ini diperoleh dari lembar validasi ahli dan angket respon peserta didik sebagai pengguna. Adapun hasil penelitian dari ketiga ahli menunjukkan kriteria sangat layak dengan rata-rata persentase sebesar 88,89% dari ahli materi, sebesar 82,78% dari ahli media, dan sebesar 95% dari ahli integrasi nilai keislaman. Dari uji coba produk skala terbatas yang dilakukan kepada 10 siswa kelas VII MTs NU Hasyim Asy’ari 03 Kudus diperoleh rata-rata persentase sebesar 98% dengan kriteria sangat layak. Maka media pembelajaran komik digital yang dikembangkan dalam penelitian ini sangat layak digunakan dalam proses pembelajaran matematika. Dengan adanya penelitian ini, diharapkan dapat mendorong para guru untuk lebih mengeksplorasi mengenai media-media pembelajaran yang mungkin digunakan dalam membantu mentransferkan ilmu pendidikan kepada siswa.